2007
DOI: 10.1007/s11270-007-9396-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Dry Deposition of Mercury in Urban Runoff

Abstract: Stormwater runoff from urban surfaces often contains elevated levels of toxic metals. When discharged directly into water bodies, these pollutants degrade water quality and impact aquatic life and human health. In this study, the composition of impervious surface runoff and associated rainfall was investigated for several storm events at an urban site in Orlando, Florida. Total mercury in runoff consisted of 58% particulate and 42% filtered forms. Concentration comparisons at the start and end of runoff events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Our finding of high particulate Hg in streams in urban settings is consistent with results of previous studies of Hg in streams that drain urban areas (Hurley et al 1998;Mason and Sullivan 1998;Lyons et al 2006), and sediment loads in the GEHR were shown to have increased with increasing development (Fusillo 1981). In mainstem surface water in the city of Berlin (sites 1 and 2), the concentrations of UTHg (20.2 and 63.3 ng/L) and UMeHg (0.35 and 2.94 ng/L) were similar to average concentrations found in urban runoff at a site in Florida, USA (Fulkerson et al 2007).…”
Section: Surface Watermentioning
confidence: 57%
“…Our finding of high particulate Hg in streams in urban settings is consistent with results of previous studies of Hg in streams that drain urban areas (Hurley et al 1998;Mason and Sullivan 1998;Lyons et al 2006), and sediment loads in the GEHR were shown to have increased with increasing development (Fusillo 1981). In mainstem surface water in the city of Berlin (sites 1 and 2), the concentrations of UTHg (20.2 and 63.3 ng/L) and UMeHg (0.35 and 2.94 ng/L) were similar to average concentrations found in urban runoff at a site in Florida, USA (Fulkerson et al 2007).…”
Section: Surface Watermentioning
confidence: 57%
“…For all metal analyses except those for total concentrations, the holding time is essential by having a critical effect on pH and on the fractionation of metals. Runoff samples were held for less than 1 h (Dean et al, 2005;Fulkerson et al, 2007), for 2-3 h (Barbosa and Hvitved-Jacobsen, 1999), for 7 h (Lau et al, 2009) or for a maximum of 24 h (Stotz, 1987;Stotz and Krauth, 1994;Booth and Leavitt, 1999;Brattebo and Booth, 2003;Flint and Davis, 2007;Moores et al, 2010;Lee et al, 2011;Nason et al, 2012;Borne et al, 2013) before delivery to a laboratory and beginning of preparation. Other studies stated the holding time as "immediately" or did not specify it properly.…”
Section: Sample Preparation and Analysismentioning
confidence: 99%
“…Mercury has drawn global attention due to its ability to contaminate entire water streams from remote trace level inputs that bioaccumulate through the food chain (Fulkerson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%